LEGAL REGULATION OF LAY JUDGES' ACTIVITIES IN THE CRIMINAL PROCESS OF UZBEKISTAN - D. J. Suyunova (Modern American Journals, 2025)
This article analyzes the procedural institution of lay judges in criminal proceedings in Uzbekistan, who participate in the consideration of criminal cases involving especially grave crimes. The study examines some organizational problems in their activities related to the administration of justice and proposes ways to address these issues. Additionally, the article explores the legislative practices of several Central Asian states and European countries regarding the involvement of jury trials or lay judges in criminal court proceedings, conducting a comparative legal analysis with Uzbekistan's national legislation. Based on the findings of the study, the author presents several proposals for improving this legal institution.
Keywords: Lay judges, criminal proceedings, especially serious crimes, trust in court, criminal cases, rich life experience.